The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/imr.12719
|View full text |Cite
|
Sign up to set email alerts
|

WHIM syndrome: Immunopathogenesis, treatment and cure strategies

Abstract: Summary WHIM syndrome is a rare, autosomal dominant immunodeficiency which is named for the four key manifestations: Warts, Hypogammaglobulinemia, Infections, and Myelokathexis. It results from heterozygous gain‐of‐function mutations in the chemokine receptor CXCR4 which is widely expressed on leukocytes and has profound influences on immune system homeostasis and organogenesis. New treatments for the disease using drugs to reduce CXCR4 function are excellent examples of precision medicine. Since CXCR4 and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 134 publications
(302 reference statements)
0
58
0
1
Order By: Relevance
“…All 17 identified mutations result in both FS and NS mutations in the C-terminal region (C-ter) of the receptor ( Figure 2) and are currently defined as WHIM-like mutations, as they closely resemble the already documented germline, activating mutations of CXCR4 C-ter occurring in heterozygosis in WHIM (warts, hypogammaglobulinemia, infection, and myelokathexis) syndrome (Online Mendelian Inheritance in Man (OMIM) 193670), a congenital autosomal dominant immunodeficiency disorder [88]. WHIM patients and their family members indeed carry several NS mutations (R334*, G336*, S338*, E343*), as well as FS (G323fs, L329fs, S339fs, S341fs) and missense (MS: E343K) mutations [89][90][91], which result in gain-of-function variants of CXCR4 [92] (see Appendix A, Figure 2). Recently, it has been reported that about 3.8% of all mutations occurring in the B-cell-receptor-CXCR4 signaling pathways identified in patients with follicular lymphoma (FL) affect the CXCR4 receptor [93].…”
Section: Waldenstrom's Macroglobulinaemiamentioning
confidence: 99%
See 3 more Smart Citations
“…All 17 identified mutations result in both FS and NS mutations in the C-terminal region (C-ter) of the receptor ( Figure 2) and are currently defined as WHIM-like mutations, as they closely resemble the already documented germline, activating mutations of CXCR4 C-ter occurring in heterozygosis in WHIM (warts, hypogammaglobulinemia, infection, and myelokathexis) syndrome (Online Mendelian Inheritance in Man (OMIM) 193670), a congenital autosomal dominant immunodeficiency disorder [88]. WHIM patients and their family members indeed carry several NS mutations (R334*, G336*, S338*, E343*), as well as FS (G323fs, L329fs, S339fs, S341fs) and missense (MS: E343K) mutations [89][90][91], which result in gain-of-function variants of CXCR4 [92] (see Appendix A, Figure 2). Recently, it has been reported that about 3.8% of all mutations occurring in the B-cell-receptor-CXCR4 signaling pathways identified in patients with follicular lymphoma (FL) affect the CXCR4 receptor [93].…”
Section: Waldenstrom's Macroglobulinaemiamentioning
confidence: 99%
“…WM is a rare form of nHL or lymphoplasmacytic lymphoma (LPL/WM) [91], with characteristic lymphoplasmacytic infiltration in the BM lymph nodes and spleen, along with the presence of monoclonal immunoglobulin M (IgM) protein in the blood [92]. The current therapeutic armamentarium relies on chemotherapy from nucleoside analogs to alkylating agents and proteasome inhibitors, and subsequently, the integration of rituximab, an anti-CD20 monoclonal antibody that now serves as the cornerstone of anti-LPL/WM regimens [93].…”
Section: Waldenstrom's Macroglobulinemiamentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue, we take an eclectic approach, drawing upon the expertise of illustrious and accomplished research groups. Most reviews focus on specific disease entities linked to single gene defects, that are now listed in the Online Mendelian Inheritance in Man (OMIM), such as DOCK8 deficiency (OMIM 611432), Complement hyperactivation, angiopathic thrombosis and protein‐losing enteropathy hyperactivation (CHAPLE, OMIM 226300), CTLA‐4 haploinsufficiency with autoimmunity and inflammation (CHAI, OMIM 616100), autoimmune lymphoproliferative syndrome (ALPS, OMIM six601859) and Ras‐associated lymphoproliferative disease (RALD, OMIM 614470) due to Fas and Ras mutations, respectively, ADA2 deficiency (OMIM 615688), Omenn syndrome (OMIM 603554) and other deficits of the recombinase activating genes RAG1 and RAG2 (OMIM 179615), warts, hypogammaglobulinemia, immunodeficiency, and myelokathexis (WHIM, OMIM 193670) syndrome due to CXCR4 mutations, autoimmune polyendocrinopathy with candidiasis and ectodermal dystrophy (APECED) due to AIRE gene mutations (OMIM 240300), Wisott‐Aldrich syndrome and actin regulatory protein deficiencies due to WAS and WIP mutations, among others . In addition, there are reviews on classes of disorders, such as allergy and atopy, common variable immunodeficiency, early‐onset inflammatory bowel disease, and Chromosome 22.q11.2 and DiGeorge syndrome .…”
mentioning
confidence: 99%